PKM PEMBUATAN PROTOTYPE PEMBANGKIT LISTRIK TENAGA ANGIN UNTUK PENERANGAN DUA DERMAGA DAN PERAHU NELAYAN TRADISIONAL DI PULAU PANJANG BANTEN - Dedy Khaerudin; Muhamad Akbar; Sinda Sundari; Islamiati Ria Amalia (Indonesian Collaboration Journal of Community Services, 2021)
The activities of the residents in general cannot be separated from the Pier and Boat, considering the main livelihood of the residents of Pulau Panjang Village, especially Kp. Peres as fishermen. The wharf is a place for residents to go back and forth from and to the island, as well as a place for loading and unloading of goods and up and down people or passengers to and from the ship both during the day and at night, while the ship itself is a means of transportation for residents, a place to carry goods, fruit products from the island and as a vehicle used by fishermen to catch fish. Both the wharf and the ship need lighting to help activities at night, especially the pier, the current condition at night is very dark without any lighting, even though Pulau Panjang Village has solar cells at 2 points, and the PLTD is not optimal. The solar cell condition is no longer functioning. While the PLTD does not supply electricity to the Pier. An alternative to this condition is to build a wind power generator (PLTB), considering that the wind potential is very good in the island area surrounded by the ocean. 1 PLTB device that is designed to produce an output of 20 volts. To illuminate the 2 piers, 8 units of generating equipment were made, while for 100 fishermen from Kp. Peres, training and coaching were made on the process of making PLTB. The activities that have been carried out have had a positive impact on all residents of Kp. Peres, Pulau Panjang Village so that the problems that Kp. The problem of electricity supply problems both at the pier and on the ship can be resolved through the manufacture of PLTB equipment. The activities that have been carried out have had a positive impact on all residents of Kp. Peres, Pulau Panjang Village so that the problems that Kp.Peres the problem of electricity supply problems both at the pier and on the ship can be resolved through the manufacture of PLTB equipment